The importance of the restorative justice approach in the resolution of medical disputes - Mawardi, Chalik; Zaid, M; Kamil , Rizqan (Faculty of Law, Universitas Slamet Riyadi, 2024)
This research aims to elucidate the imperative nature of employing restorative justice as a viable solution for addressing medical offenses. Within the framework of the Indonesian legal system, medical crimes are classified as criminal offenses that are committed within the scope of the medical profession. Specific laws and regulations prosecute these offenses. This document is the outcome of a normative legal investigation. The study's findings indicate that the law enforcement issue for medical crimes stems from the ambiguous legal provisions outlined in Law 36/2009 about health. Consequently, the enforcement of medical crimes is subject to the provisions of the Criminal Procedure Code. Consequently, it can be argued that the distinction between medical crimes and ordinary crimes in the Indonesian context remains unchanged. Moreover, it is crucial to contemplate the implementation of restorative justice as an alternative approach to addressing medical crimes, taking into account the suffering and material damages endured by victims due to the actions of others.